Cross-sectional associations between adolescents' physical literacy, sport and exercise participation, and wellbeing - Melby, Paulina S.; Elsborg, Peter; Bentsen, Peter; Nielsen, Glen (Frontiers in Public Health, 2023)
Background: Adolescence is a significant period in one’s development of positive emotional and social well-being. Physical literacy (PL) is considered a determinant of physical health and well-being and is thought to be the foundation for an individual’s engagement in physical activities. Yet, limited evidence exists on PL’s association with adolescents' health and physical activity behaviour. This study aims to 1) explore the associations between Danish adolescents’ PL and their emotional and social well-being, 2) examine whether these associations are mediated by sport and exercise participation (SEP), and 3) consider if the associations differ across sex. Methods: Cross-sectional data from a national population survey were collected in 2020. The sample consisted of 1,518 Danish adolescents aged 13–15 years. PL was assessed with the validated MyPL questionnaire. The weekly time engaged in sports and exercise was self-reported. Self-esteem, life satisfaction, body satisfaction, and loneliness were measured with items from the standardized HBSC questionnaire, and a well-being composite score was calculated from these four measures. We constructed structural equation models with PL and sports and exercise participation as independent variables and the five aspects of well-being as dependent variables. Results: Positive associations were observed between PL and SEP (β = 0.33, p < 0.001) and between PL and the five aspects of well-being with β-values between 0.19 and 0.30 (p < 0.001). These associations were greater among girls. The association between PL and four of the five well-being outcomes were partly mediated by SEP with indirect effects (β) between 0.03 to 0.05. Conclusions: Results from this study support the hypotheses that PL is important for children and adolescents’ well-being and physical activity behaviour.